The Influence of Celebrity Endorsers, e-WOM, and Brand Image on Purchase Intention for Skintific Products at Joni Cosmetic Tegal Store - Rizqi KHOERUNISA; Tabrani; Yuniarti Herwinarni HERWINARNI (International Journal of Environmental, Sustainability, and Social Science, 2025)
In an era of increasingly competitive beauty industry, consumer purchasing interest has become a crucial factor in business sustainability. This research is motivated by the decline in sales of Skintific products at Joni Cosmetic Tegal Store over the past three years, which is suspected to be related to declining consumer purchasing interest. This phenomenon prompted the researcher to examine three factors thought to influence consumer purchasing interest: the role of celebrity endorsers, electronic word of mouth (eWOM), and brand image. This study aims to determine and analyze the influence of celebrity endorsers, electronic word of mouth (eWOM), and brand image on purchase intention for Skintific products at Joni Cosmetic Tegal Store, both partially and simultaneously. This research is explanatory. Data were collected through a purposive stratified random sample using a Likert-scale questionnaire and analyzed with multiple linear regression via SPSS. The results showed that the three independent variables, celebrity endorsers, eWOM, and brand image, had a positive and significant effect, both partially and simultaneously, on consumer purchase intention. This finding demonstrates that marketing strategies involving public figures and digital information are highly influential in driving consumer purchasing decisions, particularly in the beauty industry. The study concludes that celebrity endorsers, positive consumer reviews, and strong brand image boost purchase intention for Skintific products at Joni Cosmetic Store, Tegal. Businesses are advised to maximize social media, partner with suitable public figures, and enhance brand image through consistent messaging and quality service.